The Effect Of Word Wall Media On Students’ Vocabulary Mastery At The 7th Grade Of SMPN 3 Kec. Pangkalan Koto Baru - Heni Okta Darma; Merry Prima Dewi; Loli Safitri; Widya Safitri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
One of the most crucial language components that students should master is vocabulary. It is caused vocabulary is always used in everyday activities. Nevertheless, the students have difficulty when learning vocabulary and the lack of ability of students in remembering new vocabulary in English. Based on the problems, as a resulted to conduct teaching vocabulary mastery by the use of media namely word wall to help students improving their vocabulary mastery. This research was conducted to the seventh grade of SMPN 3 Kec. Pangkalan Koto Baru. In this study, researcher used quantitative method with quasi-experimental design by comparing two classes. The subject of this study was seventh grade, namely VII1 and VII2. VII1 was experimental class with 25 students and VII2 was control class with 25 students. The research instrument was vocabulary test. The data was analyzed by using Independent Sample t-test in SPSS 26. This study indicated that there was significant difference in achievement of students’ vocabulary mastery between the students who were taught by using word wall media and without using Word Wall media. It can be seen from p-value which was smaller than the alpha value (0.000<0.05). From the results of the data, teaching vocabulary mastery through word wall media gave more significant effect to increase students’ vocabulary mastery.